ON THE EARTHQUAKE OCCURRENCES IN JAPAN AND THE SURROUNDING AREA VIA SEMI MARKOV MODELING - Panorias, C.; Papadopoulou, A.; Tsapanos, T. (Bulletin of the Geological Society of Greece, 2016)
In the present paper, the earthquake occurrences in the area of Japan, are studied by a semi Markov model which is considered homogeneous in time. The data applied refer to earthquakes of large magnitude (Mw>6.0) during the period 1900-2012. We consider 9 seismic zones derived from the typical 11 zones for the area of Japan, due to the lack of data for 3 zones (9-th,10-th and 11-th). Also, we define 3 groups for the magnitudes, corresponding to 6-7,7.1-8 and M> 8.0. Thus, we consider for our semi Markov model a finite state space, S={ ( ,)j i ZR | i=1,...9, j=1,2,3}, where i Z defines the i-th seismic zone and j R states the j-th magnitude scale. We applied the data to describe the interval transition probabilities for the states and the model's limiting behaviour for which is sufficient an interval of time of seven years. The time unit of the model is considered to be one day. Some interesting results, concerning the interval transition probabilities and the limiting state vector, are derived.